Psychological predictors of noticing and interpreting inequality in daily life - W. K. Pow, Jonathan; Y. Chen, Charlene; Nault, Kelly; J. Yap, Andy (Nature Research, 2026)
Despite growing interest in socioeconomic inequality, little research has examined how it is perceived in naturalistic, everyday settings. This study employed the Experience Sampling Method to investigate individuals’ real-time experiences of inequality, operationalized as perceptions of social class differences. Based on 6,150 momentary reports from 301 participants in Asia, we identified individual-level variables associated with these perceptions. Our findings suggest that inequality is not always salient in daily life—people do not constantly notice it, and even when they do, they may not compare themselves to others or view the differences as unfair. Notably, individual differences strongly shape these perceptions: social-comparison orientation was consistently associated with two key outcomes—attending to class differences and engaging in self-comparison. Additionally, participants with stronger power distance beliefs and greater fear-based xenophobia toward migrant workers were more likely to perceive class differences. Those scoring high on social dominance orientation, materialism, and fear-based xenophobia toward expatriates were more inclined to compare themselves to others, while those with greater fear-based xenophobia toward expatriates and stronger egalitarian beliefs (lower social dominance orientation) perceived class differences as less fair. These findings shed light on psychological mechanisms that shape how inequality is experienced and evaluated in daily life.
Keywords: 59 Ciencia Política::5906 Sociología política; ODS 10 - Reducción de las desigualdades; Perceived inequality; Social class differences; Experience sampling method; Individual differences; Social comparison; Fairness